Density functional theory meta GGA study of water adsorption in MIL-53(Cr). Issue 3 (September 2019) - Cockayne, E.
Abstract : We use density functional theory meta-generalized gradient approximation TPSS + D3(BJ) + U + J calculations to investigate the energetics and geometry of water molecules in the flexible metal-organic framework material Materials of Institut Lavoisier (MIL)-53(Cr) as a function of cell volume. The critical concentration of water to cause the transition from the large pore ( lp ) to the narrow pore ( np ) structure is estimated to be about 0.13 water molecule per Cr. At a concentration x = 1 water molecule per Cr, the zero-temperature np and lp configurations each have a hydrogen bond between the H of each framework hydroxyl group and water oxygen (O W ). At intermediate volumes, water dimer-like configurations are observed. A concentration x = 1.25 leads to hydrogen bonding between water molecules in the np phase that is absent for x = 1. Our results suggest possible mechanisms for pore closing in hydrated MIL-53(Cr).